2018
DOI: 10.1051/matecconf/201815002004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solvents on Polymorphism and Shape of Mefenamic Acid Crystals

Abstract: Mefenamic acid [2-(2, 3-dimethylphenyl) amino benzoic acid] is an active pharmaceutical compound that exist in different polymorphic form and shape. In this work the effect of solvents on polymorphism and shape of mefenamic acid crystals were examined. The solvents used were ethanol, isopropanol, ethyl acetate, dimethyl acetamide, dimethyl formamide, and acetone. Natural cooling was employed during the crystallisation process. The crystals produced were dried and analysed using optical microscopy, differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Two endothermic peaks were observed in the DSC curve of MFA crystals, one near 164 °C and the other near 229 °C. MFA is known to have crystal polymorphism [ 9 ], and it has been reported that the endothermic peak near 171 °C is the temperature at which Form I crystals transition to Form II crystals, and the peak near 231 °C is the endothermic peak due to thermal decomposition of Form II crystals [ 10 ]. In this study, peaks were observed near 164 °C and 229 °C, suggesting that the MFA used in this study is a Form I crystal ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two endothermic peaks were observed in the DSC curve of MFA crystals, one near 164 °C and the other near 229 °C. MFA is known to have crystal polymorphism [ 9 ], and it has been reported that the endothermic peak near 171 °C is the temperature at which Form I crystals transition to Form II crystals, and the peak near 231 °C is the endothermic peak due to thermal decomposition of Form II crystals [ 10 ]. In this study, peaks were observed near 164 °C and 229 °C, suggesting that the MFA used in this study is a Form I crystal ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…For a long time, only two polymorphic forms of MA were known. 5 − 7 These polymorphs can be obtained from different solvents, 8 , 9 and their solubility and dissolution rate were studied thoroughly. 10 12 Both polymorphic structures were characterized by different physicochemical methods, 13 17 and the thermal conversion of mefenamic acid from its polymorphic form I to polymorphic form II was revealed and studied by IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, only two polymorphic forms of MA were known. These polymorphs can be obtained from different solvents, , and their solubility and dissolution rate were studied thoroughly. Both polymorphic structures were characterized by different physicochemical methods, and the thermal conversion of mefenamic acid from its polymorphic form I to polymorphic form II was revealed and studied by IR spectroscopy . However, the polymorphic form I of mefenamic acid proved to be more stable than form II under ambient conditions, which causes a slow transformation of polymorph II to polymorph I . , The mechanism of this thermally dependent reversible polymorphic transition remains unclear due to the fact that the mefenamic acid molecule is disordered in the polymorphic form II .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of crystal shapes have been reported from prior experimental studies for mefenamic acid, ranging from plate-like to needle-like crystals [32][33][34]. Plates or elongated crystals of mefenamic acid were observed when crystallised from tetrahydrofuran [33], ethanol [35], ethyl acetate [30,33], dimethylacetamide (DMA) [30,34], and isopropanol [35], while needle-like crystals were often observed when mefenamic acid was crystallised from acetone [34,35]. However, many studies of the crystallisation of mefenamic acid have yielded different results for crystal shape despite using the same crystallisation solvent.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies of the crystallisation of mefenamic acid have yielded different results for crystal shape despite using the same crystallisation solvent. For example, the crystallisation of mefenamic acid from ethyl acetate carried out by Mudalip et al produced needle-like crystals [34], while the SEM pictures of mefenamic acid crystallised from ethyl acetate showed plate-like crystals in the study of Panchagnula et al [33] The latter study has also shown that the shape of mefenamic acid crystal grown from tetrahydrofuran and ethyl acetate changed as supersaturation levels changed [33]. Here, we've focused on polyhedral and needle crystal with a broad interpretation of polyhedral classification for the practical implications for downstream pharmaceutical manufacturing processes as needle-shaped crystals are more likely to cause issues during manufacturing than crystal shapes with aspect ratios closer to 1, and so are generally undesirable.…”
Section: Introductionmentioning
confidence: 99%